2010
DOI: 10.1086/655127
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Infectiousness of Tuberculosis Patients in a Directly Observed Therapy Short‐Course Program with Standardized Therapy

Abstract: Background Effective tuberculosis control is compromised by a lack of clarity about the timeframe of viable Mycobacterium tuberculosis shedding after treatment initiation under programmatic conditions. This study quantifies time to conversion from smear and culture positivity to negativity in unselected tuberculosis patients receiving standardized therapy in a directly observed therapy short-course (DOTS) program. Methods Longitudinal cohort study following up 93 adults initiating tuberculosis therapy in Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 23 publications
4
46
0
1
Order By: Relevance
“…Therefore, sputum culture status is the most reliable and useful indicator of a patient's infectiousness14. Fitzwater et al18 reported that the median conversion time from culture-positivity to culture-negativity under anti-TB medication is 37 days, which is longer than previously reported.…”
Section: Introductionmentioning
confidence: 70%
“…Therefore, sputum culture status is the most reliable and useful indicator of a patient's infectiousness14. Fitzwater et al18 reported that the median conversion time from culture-positivity to culture-negativity under anti-TB medication is 37 days, which is longer than previously reported.…”
Section: Introductionmentioning
confidence: 70%
“…The majority (>80%) of newly diagnosed TB patients treated with standard short course therapy will be sputum smear-negative by month three of treatment, 17,18 though limited data exist for HIV-infected individuals. Accordingly, the WHO recommends phenotypic DST to assess for drug-resistance in patients who remain sputum smear-positive at month three rather than month five, when programmatic notification as treatment failure would occur according to current international standards.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (>95%) of patients with fully sensitive TB are smear-negative after completing 2 weeks of effective short-course chemotherapy 110. Patients may be considered negative after at least three negative microscopic smears on separate occasions over a 14-day period.…”
Section: Treatment Of Active Tbmentioning
confidence: 99%